2018
DOI: 10.1177/2167702618757658
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Eye Movements Increase False Memory Rates

Abstract: Eye movement desensitization and reprocessing (EMDR) is a popular treatment for posttraumatic stress disorder. However, little is known about the memory effects of EMDR. Using a misinformation paradigm, we examined whether lateral eye movements, as used in EMDR, enhance susceptibility to false memories. Undergraduates (N = 82) saw a video depicting a car crash. Subsequently, participants either performed eye movements or held their eyes stationary. Afterward, all participants received misinformation in the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 31 publications
(39 reference statements)
2
47
2
Order By: Relevance
“…We saw in the introduction that some methods are recognized as possibly increasing false memories (e.g., guided imagery). Similarly, recent data have shown that the techniques used in EMDR-whose explicit objective is to reduce the emotional and traumatic impact of some memories (Shapiro, 2018)-can facilitate false memories of suggested information by therapists (Houben et al, 2018). Thus, although these are not strictly speaking recovered memories, such practices can still lead to memory distortions if the methods used are not precautionary (see Dodier & Otgaar, in press, for recommendations towards clinicians in how to interview patients with a history of trauma).…”
Section: Frequencies Of Discussion and Recovered Memories During Thementioning
confidence: 99%
See 1 more Smart Citation
“…We saw in the introduction that some methods are recognized as possibly increasing false memories (e.g., guided imagery). Similarly, recent data have shown that the techniques used in EMDR-whose explicit objective is to reduce the emotional and traumatic impact of some memories (Shapiro, 2018)-can facilitate false memories of suggested information by therapists (Houben et al, 2018). Thus, although these are not strictly speaking recovered memories, such practices can still lead to memory distortions if the methods used are not precautionary (see Dodier & Otgaar, in press, for recommendations towards clinicians in how to interview patients with a history of trauma).…”
Section: Frequencies Of Discussion and Recovered Memories During Thementioning
confidence: 99%
“…Recent works found that lateral eye movements-a technique that is central to EMDR therapy-increased false memory rates in a misinformation paradigm (Houben, Otgaar, Roelofs, & Merckelbach, 2018; but see Calvillo & Emami, in press; van Schie & Leer, in press, for failed replications). A recent meta-analysis also revealed the positive relationship between PTSD, history of trauma and depression and levels of false memory for emotional associative material (Otgaar, Murris, Howe, Merckelbach, 2017).…”
Section: Recovered Memory Therapy and Beliefs About Repressed Memorymentioning
confidence: 99%
“…In a broader sense, this is relevant to the ongoing discussion about the reliability of repressed memories (i.e., the "memory wars"; Patihis, Ho, Tingen, Lilienfeld, & Loftus, 2014). Houben et al (2018) showed 82 undergraduates a video of a car crash, after which the participants recalled what they saw either with or without simultaneous horizontal EMs. Subsequently, participants were provided with misinformation about the video in the form of an eyewitness narrative.…”
mentioning
confidence: 99%
“…In addition, Samara et al also failed to find a significant effect when using neutral valence words for stimuli (but did succeed in finding the effect for emotional words) [17]. Further, while some articles have proposed that eye movements can have the side effect of increasing false memory [e.g., 18], a recent direct replication attempt failed [19]. These failed replications are obviously of major concern and served as a main motivation for attempting to conceptually replicate the SIRE effect in our lab.…”
Section: Eye Movements and Memory Processesmentioning
confidence: 99%